1999
DOI: 10.1002/lt.500050601
|View full text |Cite
|
Sign up to set email alerts
|

Lamivudine therapy in patients undergoing liver transplantation for hepatitis b virus precore mutant-associated infection: High resistance rates in treatment of recurrence but universal prevention if used as prophylaxis with very low dose hepatitis B immu

Abstract: Recurrent hepatitis B virus (HBV)infection remains a major cause of morbidity and mortality after liver transplantation. Recently, antiviral therapy, such as lamivudine, has become available for prophylaxis against HBV reactivation posttransplantation and for the treatment of HBV recurrent disease. We report our initial experience with lamivudine therapy in patients with precore mutant-associated HBV infection undergoing liver transplantation (n ‫؍‬ 29). Outcomes were compared in three patient groups: group 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
1
5

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 38 publications
1
95
1
5
Order By: Relevance
“…These encouraging results have given rise to pilot studies in which low-dose HBIg delivered intramuscularly has been given in combination with lamivudine. 33,34 The low doses of HBIg given in these studies minimize the cost as well as adverse effects and, when used in combination with lamivudine, may ultimately prove to have advantages over the use of high-dose HBIg alone. Future studies using a combination of HBIg and lamivudine in a large enough group of patients to adequately assess treatment efficacy are needed to assess the optimal form of prophylactic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…These encouraging results have given rise to pilot studies in which low-dose HBIg delivered intramuscularly has been given in combination with lamivudine. 33,34 The low doses of HBIg given in these studies minimize the cost as well as adverse effects and, when used in combination with lamivudine, may ultimately prove to have advantages over the use of high-dose HBIg alone. Future studies using a combination of HBIg and lamivudine in a large enough group of patients to adequately assess treatment efficacy are needed to assess the optimal form of prophylactic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…10 Early experience in a small group of patients indicated that this may be effective when used in combination with lamivudine. 11 As a result, this approach been used since 1996 in most transplant centers in Australia and New Zealand.…”
mentioning
confidence: 99%
“…Numerous series reported since 1996 showed that LAM has profound antiviral activity, with complete suppression of HBV DNA in 60% to 100% of treated patients. [62][63][64][65][66][67][68] Remarkably, 6% to 45% of treated patients in some series, but not others, became HBsAg negative. 63,65,68 Viral suppression resulted in normalization of alanine aminotransferase levels in 27% to 100% of patients and significant improvement in serum bilirubin and albumin levels.…”
Section: Treatment Of Recurrent Hepatitis Bmentioning
confidence: 89%